The surgical technique and initial outcomes of Anatolian neobladder: a novel technique of ileal neobladder after radical cystectomy - Z. Talat; B. Onal; B. Cetinel; C. Demirdag; S. Citgez; C. Dogan (BMC Urology, 2018)
Abstract Background We describe a detailed novel step-by-step approach for creation of an ileal neobladder and compare the outcomes with standart neobladder. Methods Between August 2009 and January 2016, 36 consecutive patients with bladder cancer underwent radical cystectomy and orthotopic urinary diversion with an ileal neobladder. A novel technique of ileal neobladder construction, called the Anatolian neobladder, was designed by a single surgeon (ZT). Demographics and clinical data were collected. Perioperative, oncologic, and functional outcomes were reported. Complications were graded as early or late. These outcomes were compared with patients who underwent standard neobladder during this period in our center. Results The operation was technically successful in all cases. Early postoperative complications occurred in 33.3% of the patients. Daytime continence was achieved successfully in 83.3% of the patients. No patient had severe metabolic acidosis. Six patients (16.6%) died during follow-up, five due to metastatic bladder cancer and one due to a cardiac problem. There was no any statistically significant difference between novel technique and standard neobladder for oncological and functional outcomes. Conclusions The Anatolian ileal neobladder is as feasible and safe as standard neobladder technique for urinary diversion in patients with bladder cancer undergoing radical cystectomy.